Interpretation of Soil Moisture Content to Determine Soil Field Capacity and Avoid Over-Irrigating Sandy Soils Using Soil Moisture Sensors - Lincoln Zotarelli; Michael D. Dukes; Kelly T. Morgan (EDIS, 2010)
AE460, a 4-page illustrated fact sheet by Lincoln Zotarelli, Michael D. Dukes, and Kelly T. Morgan, demonstrates how to correctly interpret capacitance-based soil moisture measurement devices to accurately measure volumetric soil moisture in sandy soils common to Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, February 2010.